Claudette Colvin : I want freedom now! - Colvin, Claudette, 1939-; Hoose, Phillip M., 1947- (Farrar Straus Giroux Books for Young Readers, 2024)
"Montgomery, Alabama 1955. Fifteen-year-old Claudette Colvin is tired. Tired of white people thinking they're better than her. Tired of going to separate schools and separate bathrooms. Most of all, she's tired of having to give up her seat on the bus whenever a white person tells her to. She wants freedom NOW! But what can one teenager do? On a bus ride home from school one day, young Claudette takes a stand for justice and refuses to get up from her seat--nine months before Rosa Parks will become famous for doing the same. What follows will not only transform Claudette's life but the course of history itself." --